Pengaruh Penggunaan Teknologi Digital Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pai : (Studi Kasus di Kelas 5 SD Darul Hikam Bandung) - Yanti Nurhayati; Ghina Ulpah; Muhtadin Muhtadin; Miftahul Huda; Kemal Al Kautsar Mabruri (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Education in Indonesia is currently facing the fourth industrial revolution known as the Industrial Revolution 4.0. Education 4.0 is an education characterized by the use of digital technology in the learning process or known as the cyber system. This study aims to find out how the use of digital technology in PAI subjects at SD Darul Hikam Bandung, how is the learning achievement in PAI subjects at SD Darul Hikam Bandung, and how much influence does the use of digital technology have on PAI subjects at SD Darul Hikam Bandung. The method used in this research is descriptive analysis method with a quantitative approach. The statistics use correlation analysis, simple linear regression analysis, and the coefficient of determination and the t test. The population in this study were 103 students of grade 5 SD Darul Hikam Bandung, the sample of the study was taken as many as 50 students. The data collection technique was carried out by means of online questionnaires, interviews and documentation of the 2019/2020 odd semester PAI report cards. Based on the results of the study, it was concluded that the effect of using digital technology on student achievement in PAI subjects was included in the high category with a correlation coefficient of 0.701 and a contribution of 49.1% and the remaining 50.9%, learning achievement was influenced by other variables. There is a significant effect of the use of digital technology in PAI subjects on student achievement with a significance value of 0.000. This finding is very important, especially for PAI teachers to be able to use and apply digital technology in the teaching and learning process because the media can improve student learning achievement. For students, it is hoped that by implementing learning using digital technology, the learning achievements obtained by students can increase even higher.